Complete mitochondrial genome of the stone loach, Triplophysa stoliczkae (Teleostei: Cypriniformes: Balitoridae). (February 2013) - Li, Jiuxuan; Si, Shengjuan; Guo, Rui; Wang, Ying; Song, Zhaobin
<x xml:space="preserve">Abstract</x> The complete mitochondrial genome of the stone loach Triplophysa stoliczkae is 16, 571 bp in size, consisting of 13 protein-coding genes, 22 transfer RNA (tRNA) genes, two ribosomal RNA (rRNA) genes, and a noncoding control region. As in other vertebrates, most mitochondrial genes are encoded on the heavy strand, except for nd6 and eight tRNA genes which are encoded on the light strand. The overall base composition of the heavy strand of the T. stoliczkae mitochondrial genome is A: 28.1%, T: 29.0%, C: 25.0%, and G: 17.9%. The alignment of the Triplophysa species control regions exhibited high genetic variability and rich A+T content.